(untitled) (Modern American Journal of Medical and Health Sciences, 2026)
Angular cheilitis is a condition characterized by inflammation in the corners of the mouth, a chronic course, and frequent relapses, which in turn leads to a significant deterioration in patients’ quality of life. Numerous factors leading to the development of this disease have been studied, with microorganisms playing a key role, specifically the fungus Candida albicans and the bacterium Staphylococcus aureus. It has been established that the combined effects of these microorganisms, along with associated factors, lead to the development of angular cheilitis. This article will review studies on the onset of this pathology and the causes of frequent relapses despite treatment. Biofilms, structures that facilitate the establishment of microorganisms and the avoidance of treatment, play a key role in this process, thereby maintaining the inflammatory process. Therefore, when treating angular cheilitis, microbial factors must be considered, appropriate diagnostics must be performed, and appropriate comprehensive treatment methods must be selected, not just symptomatic relief.